Aicardi-Goutieres Syndrome A Case Report (BIRDEM Medical Journal, 2014)
A 4 month old male baby, who had episodes of generalized convulsion for 11/2 months and microcephaly, was referred to Radiology & Imaging dept. of BIRDEM for CT scan of brain. CT scan of brain showed extensive calcifications in both cerebral and cerebellar hemispheres The probable diagnosis was TORCH infection with mild generalized cerebral atrophy. TORCH screening was done and found negative. Patients RBS, SGPT, S.Calcium, Parathyroid hormone, TSH , thyroxine were within normal limits. MRI of brain showed extensive T1W hypointense and T2W hyperintense areas in peri- ventricular locations represent leukodystrophy and mild cortical atrophy of brain. CSF examination revealed WBC count 10 cells /mm3 and all the cells were lymphocytes. Aicardi Goutieres Syndrome is a rare autosomal recessive disease in which there is extensive paraventricular cerebral and cerebellar calcifications with leukodystrophy and CSF lymphocytosis. Considering history, biochemical and imaging findings the final diagnosis was Aicardi Goutieres Syndrome . DOI: http://dx.doi.org/10.3329/birdem.v4i1.18553 Birdem Med J 2014; 4(1): 43-46